The Silver Blade - Gardner, Sally (London : Orion Children's Books, 2010)
As the Revolution descends into the ferocious Reign of Terror, Yann, now an extraordinary practioner of magic, uses his skills to confound his enemies and help spirit refugees out of France, but the question of his true identity and the kidnapping of his true love, Sido, expose him to dangers that threaten to destroy him.
First published in Great Britain in 2009 by Orion Children's Books.
Young Adult.
Young Adult
Keywords: Identity (Psychology) -- Juvenile fiction; Magic -- Juvenile fiction; Romanies -- Juvenile fiction; Adventure and adventurers -- Fiction; Identity -- Fiction; Magic -- Fiction; Romanies -- Fiction; Adventure fiction; Gypsies -- Fiction; Identity -- Fiction; Magic -- Fiction; France -- History -- Revolution, 1789-1799 -- Juvenile fiction; France -- History -- Revolution, 1789-1799 -- Fiction; France -- History -- 1789-1799, Revolution -- Fiction; Adventure fiction